2009
DOI: 10.1111/j.1365-2826.2009.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Regulate Growth Hormone Secretion Via Adiponectin Receptor Mediated Ca2+ Signalling in Rat Somatotrophs In Vitro

Abstract: Obesity is associated with reduced levels of growth hormone (GH) and the disruption of pulsatile GH secretion. This results in relative GH deficiency. It is likely that a regulatory relationship between GH secretion and adipose tissue exists as the secretion of GH recovers to normal levels after a reduction in body weight. This report characterise the expression and interaction of adiponectin receptors 1 and 2 (AdipoR1 and AdipoR2) and adiponectin, respectively, in regulating the activity of GH secreting cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 59 publications
1
27
0
2
Order By: Relevance
“…Adiponectin treatment increases GHRH receptor expression in anterior pituitary cell cultures, which suggests a potential indirect regulatory role of adiponectin on GH secretion (32). Therefore, the high adiponectin levels in our model of GHRH resistance could be a compensatory mechanism to the lack of GHRH action.…”
Section: Discussionmentioning
confidence: 88%
“…Adiponectin treatment increases GHRH receptor expression in anterior pituitary cell cultures, which suggests a potential indirect regulatory role of adiponectin on GH secretion (32). Therefore, the high adiponectin levels in our model of GHRH resistance could be a compensatory mechanism to the lack of GHRH action.…”
Section: Discussionmentioning
confidence: 88%
“…To date, the presence of mRNA for adiponectin and its receptors has only been reported in rats (20,37,44), humans (37), and chickens (35). Adiponectin receptor gene expression was noted in AP and NP of cyclic gilts (19), AP of female rats (20), somatotroph cells isolated from transgenic green fluorescent protein-expressing mice, the GH3 cells (rat pituitary tumor cell line) (44), and L␤T2 (immortalized mouse gonadotrophs) (20,25). Psilopanagioti et al (34) observed the localization of AdipoRs in gonadotrophs, somatotrophs, and thyrotrophs but not in corticotrophs or lactotrophs (34).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the conflicting evidence on adiponectin's ability to cross the blood-brain barrier (23,32,43), some studies have indicated adiponectin expression in the brain and pituitary of humans, rats, mice, and chickens (5,26,37). The presence of AdipoRs in the human, pig, rat, murine, and chicken hypothalamus and pituitary suggests that adiponectin may be a factor modulating the secretory functions of central branches of hormonal axes and, indirectly, also their peripheral branches, including the HPG axis (19,24,26,34,37,43,44). Rodriguez-Pacheco et al (37) revealed that adiponectin in vitro influences growth hormone and LH secretion by the isolated anterior pituitary cells of rats.…”
mentioning
confidence: 99%
“…The precise factors that mediate these inverse relationships between GH pulsatility and adiposity in humans are not yet known. Potential mechanisms include accentuation of putatively suppressive effects of free fatty acids, IGF-I, insulin, and TNF-␣ and/or attenuation of putatively stimulatory effects of adiponectin, resistin, eucortisolemia, and leptin on GH secretion (24,36,43,54). ApEn provides a model-free and scale-invariant measure of altered feedback control in interlinked systems like the GHRH/ ghrelin/somatostatin/GH axis (14,55).…”
Section: Discussionmentioning
confidence: 99%